N-of-1 trials in cancer drug development - Gouda, Mohamed A.; Buschhorn, Lars; Schneeweiss, Andreas; Wahida, Adam; Subbiah, Vivek (Cancer discovery, 2023)
The current approaches for cancer drug development lag behind an accelerated need in the field for a fast and efficient method for evaluating drugs in the personalized medicine era. In that regard, N-of-1 studies emerge as a potential addition to the drug development arsenal, although there are several considerations before its broad application becomes feasible. In essence, N-of-1 trials are a departure from the traditional “drug-centric” model to a “patient-centric” model. Herein, we review the concept of N-of-1 trials and provide real-world examples of their use in the developmental therapeutics field. N-of-1 trials offer an exceptional opportunity for fast-tracking of cancer drug development in the precision oncology era.